Phenotyping CCL2 Containing Central Amygdala Neurons Controlling Alcohol Withdrawal-Induced Anxiety - Harper, Kathryn M.; Knapp, Darin J.; Todd, Caroline A.; Balan, Irina; Aurelian, Laure; Criswell, Hugh E.; Breese, George R. (Frontiers in Cellular Neuroscience, 2020)
Chemokines such as chemokine (C-C motif) ligand 2 (CCL2) play a role in several behaviors, including anxiety-like behavior, but whether neurons are an important source of CCL2 for behavior and neuronal CCL2 may work to effect behavior are still debated. When a Herpes Simplex Virus vector was used to knockdown CCL2 mRNA in neurons of the central nucleus of the amygdala (CeA) in rats experiencing multiple withdrawals from low dose ethanol, anxiety-like behavior appeared in the social interaction task. To examine this finding further Fractalkine (CX3CL1), a chemokine that is often found to have an opposing function to CCL2, was measured in these rats. Both alcohol withdrawal and CCL2 knockdown increased the levels of the anti-inflammatory protein CX3CL1. The combination of alcohol withdrawal and CCL2 knockdown decreased CX3CL1, alters the pro-inflammatory/anti-inflammatory balance, findings that highlight the potential importance of CCL2 and CCL2/CX3CL1 balance in anxiety. To find a mechanism by which neuronal chemokines like CCL2 could affect behavior, retrograde tracing with fluorescent nanobeads was done in two brain regions associated with anxiety the bed nucleus of the stria terminalis (BNST) and the ventral periaqueductal gray (VPAG). These studies identified CeA projection neurons to these brain regions that contain CCL2. To demonstrate that CCL2 can be transported via axons to downstream brain regions, the axonal transport blocker, colchicine, was given and 24 hours later an accumulation of CCL2 in CeA neuronal cell bodies was found. Finally, CCL2 in CeA neurons was localized to the synapse using super resolution confocal microscopy with enhanced resolution following deconvolution and electron microscopy, which along with the other evidence suggests that CCL2 may be transported down axons in CeA neurons and released from nerve terminals perhaps into brain regions like the BNST and VPAG to affect behaviors such as anxiety. These results suggest that neurons are an important target for chemokine research related to behavior.